2006
DOI: 10.1038/ncponc0511
|View full text |Cite
|
Sign up to set email alerts
|

Technology Insight: ECP for the treatment of GvHD—can we offer selective immune control without generalized immunosuppression?

Abstract: Hematopoietic stem-cell transplantation remains an important curative therapy for many conditions and its use is increasing annually. Graft-versus-host disease (GvHD) is the major cause of mortality and suffering following allogeneic hematopoietic stem-cell transplantation. Conventional treatments are associated with multiple side effects and are often ineffective. New therapeutic approaches for the control of GvHD are desperately required. Extracorporeal photochemotherapy (ECP) was developed in the 1970s for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
118
1
7

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 76 publications
1
118
1
7
Order By: Relevance
“…Our data suggest that the early use of ECP treatment during the clinical course of a disease may warrant investigation not only for GVHD, but for other diseases with deficits in Tregs, such as autoimmune diseases and solid organ rejection. 4 Our studies do not address the role of cytokines such as IL-10 or TGF-␤, or determine whether a distinct subpopulation of Tregs is responsible for reducing GVHD following infusions of ECPtreated splenocytes. Levels of serum IL-10 were unchanged 4 days following the first infusion, and its production by CD4 ϩ T cells following 60-hour coculture with both allogeneic stimulators and apoptotic splenocytes was undetectable (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data suggest that the early use of ECP treatment during the clinical course of a disease may warrant investigation not only for GVHD, but for other diseases with deficits in Tregs, such as autoimmune diseases and solid organ rejection. 4 Our studies do not address the role of cytokines such as IL-10 or TGF-␤, or determine whether a distinct subpopulation of Tregs is responsible for reducing GVHD following infusions of ECPtreated splenocytes. Levels of serum IL-10 were unchanged 4 days following the first infusion, and its production by CD4 ϩ T cells following 60-hour coculture with both allogeneic stimulators and apoptotic splenocytes was undetectable (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of GVHD has been limited either to depletion of donor T cells or the use of broadly immunosuppressive drugs that cause profound immunodeficiency as well as toxicities such as hypertension, diabetes, and aseptic bone necrosis. 4,7 ECP appears to be an effective therapy for both acute and chronic GVHD, even in some patients who are refractory to conventional immunosuppressive therapy. While randomized, controlled, multicenter studies are still needed, few side effects have been associated with ECP treatment and several reports of the efficacy of ECP for the treatment of both acute and chronic GVHD are impressive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mode of action of ECP in cGVHD remains poorly understood and may be multifactorial in nature. 9 The main proposed mechanism of action is that ECP induces apoptosis of activated T cells. The reinfusion of these cells is thought to cause immune homoeostasis through modulation of cytokine production.…”
Section: Introductionmentioning
confidence: 99%
“…Mononuclear cells are collected with a standard cell separator and UVA irradiation is performed in a laboratory setting using a stand-alone irradiator; however, no commercially available UVA irradiator is compliant with European standards marking for the sale and use of medical devices for performing ECP. While there are chain-of-custody issues and potential risks of infection associated with these 'open' photopheresis systems, there are reports of similar clinical efficacy between both techniques; however, no head-to-head comparison studies have been reported to date (93). ECP is most commonly used to treat CTCL and GVHD.…”
Section: Extracorporeal Photopheresis For the Treatment Of Autoimmunementioning
confidence: 99%